Impact of Information Technology during Covid-19 Pandemic and changing Reading Culture: Assessing Reading Habits of Students (International Journal of Food and Nutritional Sciences, 2021)
During the Covid-19 pandemic, the reading culture has changed to a great extent and the way students read also changed. The author has decided to study the changes in the reading culture of students due to the use of modern technology.In the present study it was investigated how the reading style of the students has changed. Information was collected from college female students through a questionnaire and the information was analyzed. Based on the analyzed information, it was noticed that the reading tendency of female students has decreased due to the use of electronic devices.